2007
DOI: 10.1094/php-2007-0119-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora Root Rot and Stem Canker Found on Nordmann and Subalpine Fir in Norwegian Christmas Tree Plantations

Abstract: In 2004, Phytophthora symptoms were observed on two different fir species used for Christmas trees in Norway. Isolations resulted in a Phytophthora sp. related to P. inundata from relatively newly established Nordmann fir (Abies nordmanniana) and P. megasperma from seven-year-old subalpine fir (A. lasiocarpa). The Nordmann fir plantation was more severely damaged, with approximately 70% of the trees dead or dying. In the field with subalpine fir, approximately 25% of the trees had yellow or brown foliage and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…More than 20 Phytophthora species have been associated with more than 20 different species of true firs (Farr 2022), with at least 12 Phytophthora species known to induce PRR (McKeever and Chastagner 2016). Since the mid-2000s, data available for European countries overlap with what is found in the US (Pettersson et al 2019; Shafizadeh and Kavanagh 2005; Talgø et al 2006; Talgø et al 2007; Talgø et al 2017), suggesting that either the association between these Phytophthora species and firs have been longstanding or that, as for other Phytophthora species, worldwide plant trade has contributed to their global dissemination (Bienapfl and Balci 2014; Brasier 2013; Jung et al 2016). While the information currently available connects Phytophthora species to PRR symptomatic trees, few studies have shown their pathogenic potential with Koch’s postulates (Frampton and Benson 2012; Hamm and Hansen 1982; Hoover and Bates 2013; McKeever and Chastagner 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More than 20 Phytophthora species have been associated with more than 20 different species of true firs (Farr 2022), with at least 12 Phytophthora species known to induce PRR (McKeever and Chastagner 2016). Since the mid-2000s, data available for European countries overlap with what is found in the US (Pettersson et al 2019; Shafizadeh and Kavanagh 2005; Talgø et al 2006; Talgø et al 2007; Talgø et al 2017), suggesting that either the association between these Phytophthora species and firs have been longstanding or that, as for other Phytophthora species, worldwide plant trade has contributed to their global dissemination (Bienapfl and Balci 2014; Brasier 2013; Jung et al 2016). While the information currently available connects Phytophthora species to PRR symptomatic trees, few studies have shown their pathogenic potential with Koch’s postulates (Frampton and Benson 2012; Hamm and Hansen 1982; Hoover and Bates 2013; McKeever and Chastagner 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Phytophthora cactorum and P. drechsleri have broad host ranges but are known to have differences in pathogenicity to different hosts (Chastagner, 2001;Erwin and Ribeiro, 1996). Nordmann fir has been reported susceptible to a Phytophthora species similar to P. inundata in Norway (Talgø et al, 2007), and in Hungary, a Phytophthora species lacking a name consistent with nomenclatural rules (currently referred to as P. niederhauserii) has been reported to cause sporadic disease in nordmann fir in a nursery setting (Józsa, et al, 2010). Nordmann fir is known to be variable in morphological and postharvest traits (Madsen, 1994;Nielsen and Chastagner, 2005), resistance to Phytophthora may also be a variable trait.…”
Section: Resultsmentioning
confidence: 99%
“…Phytophthora root rots of Christmas trees in Connecticut include several species, including P. abietivora, P. cactorum, P. kelmania, P. pini, and P. plurivora (McKeever andChastagner 2016, Li et al 2019). World-wide there are many more species of Phytophthora found to infect Christmas trees (Talgø et al 2007, Li et al 2019. Differences among these species with respect to their ability to infect the roots of various species of fir trees are not known, or of the variations among these species that define conditions especially conducive or restrictive for their growth.…”
Section: Introductionmentioning
confidence: 99%